A constitution of the people and how to achieve it : what Bosnia and Britain can learn from each other - Abraham, Aarif (Balkan politics and society ;, 2021)
"Britain does not have a written constitution. It has rather, over centuries, developed a set of miscellaneous conventions, rules, and norms that govern political behavior. By contrast, Bosnia's constitution was written, quite literally, overnight in a military hanger in Dayton, USA, to conclude a devastating war. By most standards it does not work and is seen to have merely frozen a conflict and all development with it. What might these seemingly unrelated countries be able to teach each other?"--